Urang Banjar Traditional Games for Health and Harmony: Learning Physical Sports and Health with Local Wisdom - Arie Rakhman; Basuki Wibawa; Rusmono; Jarudin (Global Synthesis in Education Journal, 2024)
This study aims to design and implement Sports and Health Physical Education (PJOK) learning oriented to local wisdom through the use of traditional Urang Banjar games. The local wisdom contained in the traditional game of Urang Banjar includes social, cultural, and environmental wisdom values that have colored Banjar society for centuries. The research method used was classroom action research (PTK) involving high school PJOK class students in the Banjar area. This research focuses on developing a curriculum based on local wisdom by integrating traditional Urang Banjar games as one of its main components. Data were collected through observation, interviews, and assessments of student participation in these traditional games. The results showed that the use of traditional Urang Banjar games in PJOK learning had a positive impact on students' understanding of local wisdom, physical health, and social values. Students show higher levels of participation and greater enthusiasm in this learning. In addition, they also better understand the importance of maintaining the surrounding culture and environment. In conclusion, learning PJOK oriented to local wisdom using traditional Urang Banjar games can be an effective approach to increase students' understanding of physical health, cultural values, and environmental wisdom. This supports the integration of local cultural heritage in the educational curriculum, which can produce a generation that is more insightful and has good physical health, while preserving local traditions.